A Photoconductive Thienothiophene‐Based Covalent Organic Framework Showing Charge Transfer Towards Included Fullerene1. Issue 10 (4th February 2013) - Dogru, Mirjam; Handloser, Matthias; Auras, Florian; Kunz, Thomas; Medina, Dana; Hartschuh, Achim; Knochel, Paul; Bein, Thomas
<x xml:space="preserve">Abstract</x> Filling a honeycomb: The thienothiophene‐based covalent organic framework (COF) can be loaded with a complementary semiconductor, such as a fullerene derivative, and electronic interactions are observed (see figure). The novel periodic interpenetrated donor–acceptor system shows the spectroscopic signatures of efficient charge transfer on the nanoscale. Photovoltaic activity was demonstrated upon integrating the COF:fullerene film into a device.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>